The Impact of Tobacco Smoking Upon Chronic/ Recurrent Tonsillitis and Post Tonsillectomy Bleeding - Cinamon,Udi (2017)
Abstract Introduction Smoking has many adverse effects on the oral and pharyngeal mucosa. Outcomes may be developing tonsillar infections and predisposing for post tonsillectomy bleeding (PTB). Objective The objective of our study was to determine whether smokers have more chronic/recurrent tonsillitis indicating for tonsillectomy or develop more PTB episodes. Methods We conducted a retrospective study on two groups of adults (age ≥18 years). Cohort 1: Smoking among patients who underwent tonsillectomy for recurrent/ chronic tonsillitis. Cohort 2: Smoking among patients requiring control of PTB that were operated primarily for recurrent/chronic tonsillitis. Cohort 1 served as a populationreference for the second. We retrieved the data from medical records. Results Cohort 1: 206 adults aged 18-50 years (mean 26 ± 7.6). 28% (57 patients) were smokers, versus 24% and 20% in the general population (in the years 2000 and 2010; p = 0.5, p = 0.18, respectively). Cohort 2: 114 adults aged 18-73 years (mean 26 ± 7.6). 43% were smokers, double the incidence in the general population (p = 0.004, p = 0.0004, in 2000 and 2010, respectively), and 1.5 times cohort 1 (p = 0.02). Smoking rates among bleeders on post-operative days 8-10 and later than day 10 were 53% and 60% (p = 0.0005 and p < 0.0001, respectively). Five of ten patients presenting a second PTB were smokers. Timing of re-bleedings was similar to their first PTB and dated similarly as first PTB of the entire group, mean 5.6 days (SD ± 3.2). Conclusion Smokers may encounter more chronic/recurrent tonsillitis episodes, indicating tonsillectomy and significantly are more prone for PTB. Smoking cessation may perhaps diminish recurrent/chronic tonsillitis.Whether pre-operative abstinence or its length would reduce PTB incidence is yet to be determined.